Photoionization of low-charged silicon ions. Issue 15 (January 2020) - Buhr, T; Stock, S O; Perry-Sassmannshausen, A; Reinwardt, S; Martins, M; Ricz, S; Müller, A; Fritzsche, S; Schippers, S
Synopsis: Single and multiple photoionization of Si 1+, Si 2+, and Si 3+ ions have been investigated near the silicon K-edge using the PIPE setup at beamline P04 of the synchrotron light source PETRA III operated by DESY in Hamburg, Germany. Pronounced resonance structures are observed for all ions which are associated with excitation or ionization of a K -shell electron. The experimental cross sections are compared with results from theoretical calculations.